Analysis of long-chain alcoholbiodiesel-diesel tri-fuel blends on combustion characteristics, engine performances and exhaust emissions of diesel engine - Zuhaira, Abdullah (2020)
Diesel engine is the main source of energy propulsion that is used for automobile transportations, heavy industries and agriculture machinery. It is well known for its friction efficient and high performance in combustion. Additionally, it is also known for its advantages in terms of high torque, high efficiency, as well as reliability with low operating cost. However, based on the energy crisis of production diesel fuel (DF) from fossil fuels, it has been predicted that the world’s fossil fuel reservoir would be depleted in 2070. Other than that, fossil fuel is the primary source that is non renewable and nonreusable, which current stock is very limited. In addition, the disadvantages of engine performance when DF was blended to short-chain alcohol and different volume ratio of fuel blends. In order to address these issues, in this study, a various blend of long-chain alcohol-biodiesel-diesel tri-fuel blends were analysed based on combustion characteristics, engine performances and exhaust emissions. The current study has three objectives; (i) to determine the stability and thermo-physical of D85-B10-PE5, D80-B10- PE10, D75-B10-PE15, D85-B10-HE5, D80-B10-HE10 and D75-B10-HE15, (ii) to investigate the combustion characteristics, engine performances and exhaust emissions of long-chain alcohol-biodiesel-diesel tri-fuel blends, and (iii) to determine the optimum blends ratio of D85-B10-PE5, D80-B10-PE10, D75-B10-PE15, D85-B10-HE5, D80- B10-HE10 and D75-B10-HE15 based on engine performance by using Response Surface Methodology (RSM) software. The test was conducted on YANMAR TF120M engine single cylinder, and direct injection diesel engine. The experiments were conducted on five engine loads of 0%, 25%, 50%, 75% and 100% at constant engine speed of 1800 rpm. The test fuel consists of 5%, 10% and 15% volume ratio of pentanol and hexanol, added with remaining 10% constant volume ratio of palm oil methyl ester (POME), and blended with 85%, 80% and 75% of DF, named fuel as D85-B10-PE5, D80-B10-PE10, D75-B10-PE15, D85-B10-HE5, D80-B10-HE10 and D75-B10-HE15. The overall results are then compared with DF and B100 as the baseline. The result of stability observation reveals that D85-B10-PE5, D80-B10-PE10, D75-B10-PE15, D85-B10-HE5, D80-B10- HE10 and D75-B10-HE15 did not show any phase separation. The thermo-physical properties compared to the B100, calorific value increased by 11.45% and 11.38% for the D80-B10-PE10 and D75-B10-HE15 respectively. Also, the kinematic viscosity of D80- B10-PE10 and D75-B10-HE15 showed a reduction of 27.96% and 23.23% respectively, due to the addition of long-chain alcohols. In addition, in-cylinder pressure at 100% engine load, showed maximum peak pressure in D75-B10-PE15 and D85-B10-HE5 decreases by 0.66% and 0.54% compared to DF. This is due to higher in-cylinder pressure temperature that weakened the cooling effect of addition long-chain alcohol. The maximum heat release rate showed D75-B10-HE15 increased by 31.98% compared to DF at 100% engine load. Furthermore, the engine performance in terms of brake thermal efficiency increased by 10.37%, while brake specific fuel consumption decreased by 13.75% for D80-B10-PE10 compared to DF at 100% engine load. Besides, the reduction in exhaust emissions that produced CO2, and NOx decreased by 6.79% and 20.65% for D75-B10-PE15 at 100% engine load compared to DF. This is due to the lower cetane number and viscosity that is at highest volume concentration of long-chain alcohol. Lastly, the best selection of optimum blend ratio is close to D80-B10-PE10 and D75- B10-HE15.